Gibbs-Wilbraham Phenomenon in Square Wave Function - Budha, Bhupendra; Subedi, Man Bahadur (Journal of the Institute of Engineering, 2018)
The aim of this paper is to show the fluctuation on overshoots of particular term due to change in magnitude of discontinuity in the square wave function represented in Fourier series and also is to address the mathematical relation between those parameters. Along with that, some graphical plots of different terms are given to illustrate the results and to interpolate data with smooth curves using Cubic spline interpolation in MATLAB. Journal of the Institute of Engineering, 2018, 14(1): 206-215